2022
DOI: 10.5603/cj.a2020.0005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of readiness to discharge from hospital on adherence to treatment in patients after myocardial infarction

Abstract: Background:The healthcare professionals involved in in-hospital treatment of myocardial infarction (MI) are also responsible to patients for their education before leaving the hospital.This education aims to modify patient behaviour in order to reduce relevant risk factors and improve self-control and adherence to medications. The aim of the study was to analyse the relationship between readiness for discharge from hospital and adherence to treatment at follow-up in MI patients. Methods: An observational, sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…In our study, we did not show that the level of knowledge of patients on the day of discharge affected compliance with therapeutic recommendations in the field of pharmacotherapy after 6 months of observation. On the other hand, another study analyzing the impact of readiness for discharge on adherence showed that an increase in the objective assessment of patients' knowledge (RHD-MIS subscale) affects a higher level of compliance [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not show that the level of knowledge of patients on the day of discharge affected compliance with therapeutic recommendations in the field of pharmacotherapy after 6 months of observation. On the other hand, another study analyzing the impact of readiness for discharge on adherence showed that an increase in the objective assessment of patients' knowledge (RHD-MIS subscale) affects a higher level of compliance [23].…”
Section: Discussionmentioning
confidence: 99%
“…Its elimination might largely improve the clinical and economical outcomes of treatment [ 8 , 16 ]. Recognizing the importance of this problem, our team have conducted a wide spectrum research in this field [ 6 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presented data were collected as a part of the research project "Impact of educational intervention on adherence to therapeutic recommendations". Some results of this project have already been published [11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%